Study of Legal Assurance of Transfer of Shares in a Public Company that is a Joint Property without the Approval of the Partner - Suheri Mira Atmaja; Muhammad Arifin; T. Erwinsyahbana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Shared property in marriage, is a concept derived from customary law in Indonesia. In addition, this is stated in Law No. 1 of 1974 on Marriage. Not only that, Islamic law also regulates the common property in marriage. However, the joint assets included in the limited liability company's shares, are still a matter of debate. Based on Law No. 40 of 2007 concerning Limited Liability Companies, it is known that shares cannot be transferred to other parties, which means, shares are not included in the joint property. This research, therefore, wants to analyze the juridical status of shares as a common property in a marriage. Research is done with descriptive analysis. The results of the study found that the juridical status of shares as a common property in a marriage is expressly not contained in existing laws and regulations, but if viewed in Article 60 paragraph (1) of the UUPT which stipules that shares are moving objects and give rights to their owners, then if the shares are acquired during the marriage period, Research is done with descriptive analysis. The results of the study found that the juridical status of shares as a common property in a marriage is expressly not contained in existing laws and regulations, but if viewed in Article 60 paragraph (1) of the UUPT which stipulates that shares are moving objects and give rights to their owners, then if the shares are acquired during the marriage period.